Tackling the Major Challenges in Learning Target Language and Utilizing Efficient Methods - Qurbonova Gulnoza Ahmadjon qizi (Researchparks Publishing, 2022)
Learning a foreign language is one of the most important issues today. In particular, it is not in vain that this area is considered at the level of public policy. This article describes in detail the properties and methods of the target language.